The Extent and Reasons for Dissatisfaction From Outpatients Provided With Pharmacy Services at Two Public Hospitals in Eastern Ethiopia - Nigussie, Shambel; Edessa, Dumessa (Frontiers in Pharmacology, 2018)
Background: Satisfaction of patients for pharmaceutical services reflects their preferences and expectations, and the realities of care. It is critical to understand the extent of dissatisfaction for pharmaceutical services and its associated factors in order to optimize the required quality of the services provided. Therefore, this study is aimed to explore the extent and reasons for dissatisfaction from outpatients with the pharmacy services provided at Hiwot Fana Specialized University Hospital and Federal Harar Police Hospital in Harar, eastern Ethiopia. Methods: An institution-based cross-sectional study was conducted on 844 outpatients. Data were collected by interviewer administered interviews that employed a structured questionnaire which was meant to estimate dissatisfaction/satisfaction of the outpatients for the pharmacy services provided using a 1–5 point LIKERT scale. SPSS version 20.0 was employed to analyze data. Accordingly, potential covariates were identified using chi-squared test and binary logistic regression analyses were undertaken to adjust for the covariates. Results: The highest (61.1%) dissatisfaction was scored for lack of consistent availability of prescribed drug(s). Factors that showed significant association with dissatisfaction were marital divorce (adjusted odds ratio AOR 2.67; 95% CI 1.01–7.06); lack of quality system or Auditable Pharmaceutical Transaction Services (AOR 13.56; 95% CI 9.10–20.23); and patients’ perceived insufficient knowledge of pharmacists (AOR 2.50; 95% CI 1.61–3.87) and good interaction with their pharmacists (AOR 0.28; 95% CI 0.14–0.56). Conclusions: Outpatients’ highest dissatisfaction was related with the inadequate availability of prescribed drug(s). Lack of quality system; marital divorce; and patients’ perceived insufficient knowledge of pharmacists increased the likelihood of dissatisfaction but it was less likely to occur in outpatients who perceived their interaction with pharmacists as positive. Therefore, in addition to securing consistent availability of drugs and implementing a quality system, improving the technical and personal skills of pharmacists is likely to improve satisfaction of patients with the pharmacy services.